RESEARCH ＆ APPLICATION OF SERVICE-LOADS ENVIRONMENT FOR COMMERCIAL VEHICLE BASED ON NON-PARAMETRIC KERNEL DENSITY ESTIMATION METHOD - LUAN ShiJie; YU JiaWei; ZHENG SongLin; JING Qing (Jixie qiangdu)
Research and establishment of customer service road-load characteristics are foundation and precondition for reasonable lightweight design of automotive structure strength. Traditionally method mostly based on parametric probability density estimation method to analyze statistical characteristics of customer service road-load. Based on large-scale data research of customer service road-load characteristics of a commercial vehicle,parametric and non-parametric method were respectively applied to study the probability density distribution model of typical customer service road-load characteristics. The results showed that the non-parametric method describe the customer service road-load characteristics more accurately than the parametric method. Therefore,the non-parametric method was applied to calculate the 90 th percentile of customer service characteristics. By applying non-parametric rain-flow matrix extrapolation method,the whole service life loads of shock absorber spring were estimated based on collected road loads data,and fatigue-testing specification was established. The results can provide reference for establishing the automotive structure fatigue testing specifications reasonably under the concept of user-association.